Răspuns :
Răspuns:
a)
[tex]( x - 1)(x + 1) = {x}^{2} - {1}^{2} = {x}^{2} - 1[/tex]
b)
[tex](x + 2)(x - 2) = {x}^{2} - {2}^{2} = {x}^{2} - 4[/tex]
c)
[tex](x + 3)(x - 3) = {x}^{2} - {3}^{2} = {x}^{2} - 9[/tex]
d)
[tex](5 - x)(x + 5) = {5}^{2} - {x}^{2} = 25 - {x}^{2} [/tex]
e)
[tex](2x + 1)(x + 2) = 2x(x + 2) + 1(x + 2) = 2 {x}^{2} + 4x + x + 2 = 2 {x}^{2} + 5x + 2[/tex]
f)
[tex](1 - x)(5 x - 4) = 1(5x - 4) - x(5x - 4) = 5x - 4 - 5 {x}^{2} - 4x = 5 {x}^{2} - x - 4[/tex]
Răspuns:
a) (x-1)(x+1)=x^(2)-1
b) (x+2)(x-2)=x^(2)-2^(2)=x^(2)-4
c)(x+3)(x-3)=x^(2)-9
3^(2)=9
d) (5-x)(x+5)=(5-x)(5+x)=5^(2)+x^(2)=25-x^(2)
adunarea este comutativă 5+x=x+5
e) =2x^(2)+4x+x+2=2x^(2)+5x+2
f) =5x-4- 5x^(2)+4x= -5x^(2)+9x-4
Explicație pas cu pas:
La a),b),c),d) folosim (a+b)(a-b)=a^(2)-b^(2)